Cotton waste research follows the effect of pre-treatment and the observation of physical appearance - Mahamude, A. S. F.; W. S., W. Harun; K., Kadirgama; D., Ramasamy; Farhana, K. (IOP Publishing, 2021)
This paper aims to evaluate the waste cotton quality and its commercialization. The recycled cotton demand seems to be increased day by day: although the lower quality of the resulting items is the biggest barrier to cotton recycling. A thorough analysis of recycled cotton processes is therefore necessary from separation/shredding to completion. To that end, textile wastes made of pre-consumer cotton were systematically collected from the spinning mill. After pretreatment of cotton waste cellulose by caustic soda, alkali, and detergent in 100°C temperature for 30 minutes have produced white clean cotton. Following the next process by sodium hydroxide and isopropyl alcohol must produce Carboxymethyl Cellulose (CMC). CMC has big use in Textile printing, finishing, and warp sizing even in Ice-cream and food baking industry. Recent success stories will be addressed with the steady cotton processing to altering the properties of cell wall cotton and cotton fiber. The prospects of conducting experiments of waste cotton and checking the properties of treated cotton have a great value in the production of commercial products and the results relived that the value addition of waste cotton is a very easy method.